Réponses

2014-01-18T00:39:58+01:00
Bonsoir

A=72,4 x 10puissance -6

A=72,4\times10^{-6}=7,24\times10\times10^{-6}=7,24\times10^1\times10^{-6}\\\\=7,24\times10^{1-6}=7,24\times10^{-5}

B=0,012 x 10puissance 5

B=0,012 \times10^5=1,2\times10^{-2} \times10^5=1,2\times10^{-2+5}=1,2\times10^{3}


C=654 x 10puissance -5

C=654\times 10^{-5}=6,54\times10^2\times 10^{-5}=6,54\times 10^{2-5}=6,54\times 10^{-3}
2014-01-18T00:54:55+01:00
A=72,4 x 10puissance -6 = 7,24 x 10puissance -5
B=0,012 x 10puissance 5
=1,2 x 10puissance 3
C=654 x 10puissance -5
= 6,54 x 10puissance -3

En espérant t'avoir aidé.